2015
DOI: 10.4238/2015.august.19.30
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication Proline accumulation is a general response to abiotic stress in the date palm tree (Phoenix dactylifera L.)

Abstract: ABSTRACT. Plants exposed to certain abiotic stress conditions tend to produce the amino acid proline, which acts as an active osmolyte, a metal chelator, an antioxidant, and a signaling molecule. There is increasing evidence that proline accumulates in plants due to a wide range of abiotic stress, in particular high soil salinity and drought. Therefore, proline content is often used as a marker-assisted breeding tool aimed at improving drought and salinity tolerance. In this study, it was investigated whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 22 publications
(21 reference statements)
6
66
2
Order By: Relevance
“…Production of proline is a common response to various abiotic stresses and its differential accumulation cannot be used as a molecular marker in date palm breeding programs aimed at improving drought or salinity tolerance traits in date palms. This conclusion is consistent with the theory that the molecular outcomes of abiotic stresses are often nonspecific [17]. …”
Section: Introductionsupporting
confidence: 92%
“…Production of proline is a common response to various abiotic stresses and its differential accumulation cannot be used as a molecular marker in date palm breeding programs aimed at improving drought or salinity tolerance traits in date palms. This conclusion is consistent with the theory that the molecular outcomes of abiotic stresses are often nonspecific [17]. …”
Section: Introductionsupporting
confidence: 92%
“…Proline generally acts as an osmolyte for osmotic adjustment, as well as stabilizing sub-cellular structures including membrane and proteins (Ashraf and Foalad, 2005;Yaish, 2015). Accumulation of free proline under salt stress has been correlated with salt tolerance; our findings are in accordance with many other results which revealed that date palm callus accumulates a significant amount of proline as a response to NaCl stress (Al-Khayri, 2002;AlMansoori and Eldeen, 2007;Jasim et al, 2010;Al-Bahrany and Al-Khayri, 2012;Yaish, 2015).…”
Section: The Effect Of Acf and Nacl Concentrations On Callus Browningsupporting
confidence: 89%
“…It is remarkably high when leaves are exposed to suboptimum temperatures and salinity stress. These results indicate that the production of proline is a common response to various abiotic stresses (Yaish 2015). Addition of K + to the salt containing media of date palm has reduced the absorption of Na + and also balanced ions compartmentalization.…”
Section: Introductionmentioning
confidence: 80%